Dispersions of carbon nanotubes in cholesteric liquid crystals with photoactive components - Samoilov, A.N.; Minenko, S.S.; Lisetski, L.N.; Lebovka, N.I.; Soskin, M.S.; Torgova, S.I. (Functional Materials, 2014)
Optical transmission and selective reflection data are reported for dispersions of single-walled carbon nanotubes (SWCNT) in cholesteric liquid crystals comprising a mixture of cholesterol esters and azoxy nematic ZhK-440. The optical density was shown to be essentially non-linear with SWCNT concentration, with a minimum ascribed to formation of "stacked" aggregates of nanotubes. The location of this minimum, as well as the selective reflection maximum (helical pitch), are sensitive to partially reversible UV-induced trans-cis-trans isomerisation effects. The UV-controlled helical pitch variation was shown to be only slightly affected by introduction of carbon nanotubes. Application prospects of such materials in optoelectronic devices are considered.